KETERLIBATAN MASYARAKAT LOKAL DALAM PENGEMBANGAN POTENSI WISATA DI KABUPATEN SEMARANG - Utami, Santi Muji (Faculty of Social Science, Universitas Negeri Semarang, 2013)
The majority of tourism in Semarang district, gives us diversity in culture, nature, historical treasures which deserve to be considered as a regional tourist destination in Central Java. The potential for historical, cultural and natural tourism in Semarang district, when developed optimally can be aligned with tourism destination of Yogyakarta and SurakartaResearch results indicate that the potential for tourism in Semarang District is various which consists of nature tourism, historical tourism, cultural tourism, artificial, agro tourism and travel industry. Improving the quality and quantity of infrastructure are continued, albeit not optimal. The involvement of local communities in addition to participating in the consevation and development of tourist attraction,Â also givesÂ influence on social change, economic growth, the level of household economy life and welfare of local communities.